A comment on Prescott's call for prudence and rigor when measuring emotions. (December 2017) - Delplanque, Sylvain
Highlights: Researchers in affective sciences have long been confronted to emotion definitions and measures issues. Prescott's article encourages sensory analysis researchers to be prudent when measuring emotions. I would like to contribute further arguments going in the same direction.